2020
DOI: 10.3389/fphys.2020.604069
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Fission and Mitophagy Coordinately Restrict High Glucose Toxicity in Cardiomyocytes

Abstract: Hyperglycemia-induced mitochondrial dysfunction plays a key role in the pathogenesis of diabetic cardiomyopathy. Injured mitochondrial segments are separated by mitochondrial fission and eliminated by autophagic sequestration and subsequent degradation in the lysosome, a process termed mitophagy. However, it remains poorly understood how high glucose affects the activities of, and the relationship between, mitochondrial fission and mitophagy in cardiomyocytes. In this study, we determined the functional roles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 57 publications
(103 reference statements)
2
25
1
Order By: Relevance
“…The enhanced MFN2 expression increased the mitochondrial fusion while reducing fission, and this has been reported to decrease glycolysis during the cardiac fibroblast activation (Gao et al, 2020). Previous studies found that HG-induced mitochondrial fission in various cell types, (Kobayashi et al, 2020;Wu Q. R. et al, 2021) and these may further support the MAM-independent effects in the study. Therefore, it should be noted that the alterations of mitochondrial fusion and fission may independently induce mitochondrial respiration and inhibit glycolysis.…”
Section: Discussionsupporting
confidence: 71%
“…The enhanced MFN2 expression increased the mitochondrial fusion while reducing fission, and this has been reported to decrease glycolysis during the cardiac fibroblast activation (Gao et al, 2020). Previous studies found that HG-induced mitochondrial fission in various cell types, (Kobayashi et al, 2020;Wu Q. R. et al, 2021) and these may further support the MAM-independent effects in the study. Therefore, it should be noted that the alterations of mitochondrial fusion and fission may independently induce mitochondrial respiration and inhibit glycolysis.…”
Section: Discussionsupporting
confidence: 71%
“…In myocardial tissue, mitochondria provide energy for the normal continuous activities (contraction and relaxation) of cardiomyocytes ( Kowaltowski, 2019 ; Hughes et al, 2020 ; Jusic and Devaux, 2020 ). Mitochondrial dysfunction is an important contributor to the pathogenesis of myocardial stress, together with oxidative stress, protein misfolding, and inactive protein denaturation ( Zhou et al, 2017a ; Kobayashi et al, 2020 ; Ma et al, 2020b ; Wang et al, 2020b , c ). The accumulation of reactive oxygen species promotes the mutation of mitochondrial DNA ( Wang et al, 2019a ; Chang et al, 2020 ; Szaraz et al, 2020 ), while the disruption of the tricarboxylic acid cycle depletes the cellular energy supply and accelerates cellular aging ( Cao et al, 2019 ; Mukwaya et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial dysfunction is a hallmark of neurodegeneration in PD patients. There are various processes (fission, biogenesis, and mitophagy) that regulate mitochondrial quality within all cell types (Kobayashi et al, 2020). Fission is a mechanism that activates mitophagy and plays an adaptive role in the clearance of damaged mitochondria in response to oxidative stress or injury.…”
Section: Mitochondrial Response To Mptp In Dopaminergic Neuronsmentioning
confidence: 99%